(untitled) (Global Journals of Research in Engineering, 2019)
Sustained economic growth coupled with inadequate public transport service are the main factors that contribute to increasing private vehicle dependency in Metro Manila These issues exacerbate traffic congestion and spur higher energy demand resulting in more greenhouse gas GHG production This paper developed a multinomial logit MNL -based household vehicle ownership model and a linear regression-based household energy demand model taking account of urban form attributes gas price and vehicle cost